ANALISIS EFEKTIVITAS MODEL THINK PAIR SHARE (TPS) TERHADAP PENINGKATAN KEMAMPUAN KOGNITIF SISWA BERDASARKAN GAYA BELAJAR MATERI PERKALIAN KELAS V SDN NGADIREJO 02 MADIUN - Angga Asyhari Wardanu; Rissa Prima Kurniawati; Elly’s Mersina Mursidik (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Cognitive ability is very important for students to understand lesson concepts, especially in mathematics. At SDN Ngadirejo 02, problems were found such as students' lack of enthusiasm and less varied teaching methods, which impacted their cognitive abilities. This study aims to analyze the effectiveness of the Think Pair Share (TPS) learning model in improving the cognitive abilities of fifth-grade students on multiplication material, considering students' learning styles. The method used was an experiment with a true experimental design, involving two sample classes: an experimental class and a control class, each consisting of 17 students. Data were collected through tests, questionnaires, and documentation, with learning outcomes obtained from post-tests after the implementation of the learning model. The results showed a significant difference in cognitive ability between students using the TPS model and those using the lecture method, with the experimental class’s average post-test score of 84.41 compared to 53.82 in the control class. Additionally, learning styles also influenced learning outcomes. In conclusion, the TPS model effectively improves students' cognitive abilities, especially when adjusted to their learning styles.